Australian and Indian nursing students' skills and attitudes surrounding mental illness: Preparing for a transnational nursing education collaboration. (January 2021) - Patterson, Christopher; Perlman, Dana; Moxham, Lorna; Sudhakar, Christopher; Nayak, Asha K.; Velayudhan, Binil; Jose, Tessy Treesa; Tapsell, Amy
Abstract: Cultural competence is a viewed as a necessary set of skills within nursing, and there is a need for student support in this area. This is particularly important in mental health care, with two skills considered crucial for providing quality care: therapeutic relationship skills and positive attitudes. With the objective of initiating an educational collaboration between two educational institutions, this study examined Australian and Indian undergraduate nursing student's perceived therapeutic relationship skills and stigma attitudes associated with mental illness. Participants were five hundred and fifty-five ( n  = 555) undergraduate nursing students from two different universities in Indian and Australia. The modified version of the Scale To Assess Therapeutic Relationship (STAR-C) and the Social Distance Scale (SDS) were both used to examine student's perceived therapeutic relationship skills and stigma attitudes. Australian nursing students indicated lower levels of stigma with lower levels of self-reported therapeutic relationships skills, as compared with the Indian nursing student cohort. However, Indian nursing students indicated higher levels of stigma with higher self-reported therapeutic relationship skills. The results of this study may reflect cultural differences and meanings attached to mental illness. Highlights: Transnational collaborations may foster cultural competency, skills and attitudes between educational institutions. This study compared Indian and Australian nursing student attitudes and skills in relation to mental health. Indian and Australian students differed in their perceived therapeutic relationship skills and attitudes. Cultural differences in nursing skills and attitudes must be considered to ensure quality transnational care.